Ab Initio Spin-Polarized calculations of Fluorine Trimers on Graphene - Rivera Julio, Jagger (2015)
We studied the magnetic states of fluorine trimers on graphene by using spin-polarized density functional calculations. We considered the absorption of fluorine atoms on one side of the graphene sheet (cis-clusters). Several possible positions of the fluorine atoms were considered to find the most energetically favorable configuration, and its different metastable magnetic states were investigated.